2018
DOI: 10.1007/s11274-018-2543-3
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient phenol degradation in a batch moving bed biofilm reactor: benefiting from biofilm-enhancing bacteria

Abstract: In this study, the efficiency improvement of three moving bed biofilm reactors (MBBRs) was investigated by inoculation of activated sludge cells (R1), mixed culture of eight strong phenol-degrading bacteria consisted of Pseudomonas spp. and Acinetobacter spp. (R2) and the combination of both (R3). Biofilm formation ability of eight bacteria was assessed initially using different methods and media. Maximum degradation of phenol, COD, biomass growth and also changes in organic loading shock were used as paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…30 Bacteria in biofilms exhibit robust resistance to antibacterial agents, and phenols have been shown to enhance biofilm formation in Streptococcus mitis, Fusobacterium nucleatum, and Porphyromonas gingivalis. 31,32 Surprisingly, our results indicated a notable absence of black colonies in the presence of 0.5, 1, and 2 mM 2,4-DTBP on Congo red agar (Figure 2C), suggesting their ability to inhibit biofilm formation. Previous studies have elucidated the inhibitory effects of phenol, including the disruption of cell membranes.…”
Section: Effect Of 24-dtbp On the Growth And Morphologicalmentioning
confidence: 68%
“…30 Bacteria in biofilms exhibit robust resistance to antibacterial agents, and phenols have been shown to enhance biofilm formation in Streptococcus mitis, Fusobacterium nucleatum, and Porphyromonas gingivalis. 31,32 Surprisingly, our results indicated a notable absence of black colonies in the presence of 0.5, 1, and 2 mM 2,4-DTBP on Congo red agar (Figure 2C), suggesting their ability to inhibit biofilm formation. Previous studies have elucidated the inhibitory effects of phenol, including the disruption of cell membranes.…”
Section: Effect Of 24-dtbp On the Growth And Morphologicalmentioning
confidence: 68%
“…On the one hand, the results indicated that the method of multiple addition could ensure higher microbial activity to degrade more OM than that using one-time addition. Sahar et al came to a similar conclusion about multiple addition measure to promote performance of pollutant purification in biological strengthening technology [42]. On the other hand, appropriate aeration could further improve the removal rate of OM in sediment.…”
Section: Effects Of Dosage Methods On Removal Of Om In Sedimentmentioning
confidence: 84%
“…The moving bed biofilm reactor (MBBR) is a wastewater treatment process that uses plastic carriers with a buoyancy close to water to support the development of the bioactive microbial biofilm [3,4]. This MMBR technology benefits by inoculation with bacterial strains with organic pollutant degradation ability and promoting biofilm formation [5][6][7].…”
Section: Introductionmentioning
confidence: 99%